PEMBENTUKAN ORGANISASI PERSAMPAHAN DALAM PERENCANAAN SISTEM PENGELOLAAN SAMPAH 3R BERBASIS MASYARAKAT (STUDI KASUS KELURAHAN SUNGAI BARU, KOTA BANJARMASIN) - Ratna Ayu Sylvia Resty; Winardi Dwi Nugraha; Endro Sutrisno (Jurnal Teknik Lingkungan, 2013)
AbstractSungai Baru Village is one of villages in the city of Banjarmasin that waste management is still using the old paradigm that is gathering, transportation, waste. In addition, the waste dumped into the back of the house and then dumped or incinerated. Even some that waste dumped into the river for that it needs to be done managing. Suitable alternative to be implemented in Sungai Baru Village is a community-based solid waste management with the implementation of the 3 R as waste is managed and utilized within the village so no need to be transported to the outside. In addition, provide additional income for the citizens and community, so that people can be channeled abilities. In order to increase the active role of the community, it needs to be done about the trash socialization and established a waste management organization in the Sungai Baru Village, which formed its staff based on the desire and willingness Villagers.